2012
DOI: 10.1590/s0004-282x2012000200011
|View full text |Cite
|
Sign up to set email alerts
|

Language disorders and brain lesion topography in aphasics after stroke

Abstract: Aphasia is a language disorder associated with focal brain lesions. Although the topographic definition of the language area has been widely accepted, there is not necessarily any direct correlation between the lesion site and the manifested symptoms. Objective: To analyze aspects of language in aphasics in relation to lesion topography. Methods: A prospective, descriptive study of qualitative nature was conducted on 31 individuals, aged older than 15 years, with at least three years of schooling, and a confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…The study of Devido-Santos et al 1 suggested that there was no direct relationship between lesion topography and stroke aphasia type in their sample, in contrast with the large amount of scientific knowledge accumulated since Paul Broca' s descriptions of brain-language relationships in which classic aphasias have been correlated to specific brain regions [3][4][5][6] . It is true that a number of traditional concepts regarding mechanisms of aphasia are inconsistent with now abundant data.…”
Section: Dear Editorsmentioning
confidence: 89%
See 1 more Smart Citation
“…The study of Devido-Santos et al 1 suggested that there was no direct relationship between lesion topography and stroke aphasia type in their sample, in contrast with the large amount of scientific knowledge accumulated since Paul Broca' s descriptions of brain-language relationships in which classic aphasias have been correlated to specific brain regions [3][4][5][6] . It is true that a number of traditional concepts regarding mechanisms of aphasia are inconsistent with now abundant data.…”
Section: Dear Editorsmentioning
confidence: 89%
“…First of all, we congratulate Devido-Santos et al 1 by their interesting paper. Until recently, our understanding of how language is organized in the brain depended on analysis of language deficits in patients with fortuitously placed lesions.…”
Section: Dear Editorsmentioning
confidence: 91%
“…However, from 1861 to date, not enough progress has been done in relation to aphasia theoretical and technical consistency (Crary and Wertz 1992;Crockett et al 1981;Crosson et al 2007;Démonet et al 2005;Devido-Santos et al 2012;Grodzinsky 2006;Judas and Cepanec 2007;Keller et al 2009;Kuest and Karbe 2002;Poeppel and Hickok 2004;Price et al 2011;Rohrer et al 2008;Roth 2002;Smits et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Estudios 4,5 , apoyados en exámenes de neuroimagen funcional, sobre lesión neurológica asociada a tareas cognitivas, indican que el procesamiento del lenguaje no depende solo de las áreas de Broca y Wernicke, pero también del trabajo conjunto de distintas áreas cerebrales, tal como fue postulado por los estudios clásicos de Luria.…”
unclassified
“…La afasia es un síndrome consecuente de una lesión focal cerebral y se manifiesta con señales de trastornos tanto de la comprensión como de la expresión del lenguaje oral y escrito, en diferentes niveles y grados de severidad 5,6 . Es una secuela común en los casos de accidente cerebrovascular (ACV) que interfiere en las tareas académicas, ocupacionales, laborales y en la vida social del sujeto 5,6 .…”
unclassified